Field application of entomopathogenic agents against the fall armyworm (Spodoptera frugiperda) (J. E. Smith) (Lepidoptera: Noctuidae) in maize - Ahmed Azazy; Ahmed Adly; Ibrahim El Sappagh; Abdelhalim Khalil; Hassan El-Saadany (Egyptian Journal of Biological Pest Control)
Abstract Background Fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae), larvae have the potential to significantly reduce maize yields. The FAW has become resistant to pesticides and environmental pollutants, making chemical management of the insect useless. Safe and efficient substitutes are desperately needed to manage FAW caterpillars on maize. Entomopathogenic agents, such as nematodes, fungi, and bacteria, provide a promising and sustainable option. The entomopathogenic agents were evaluated for control of the FAW, S. frugiperda, in corn field. Results Possibility of controlling FAW by applying easily applied bioagents to the whorl of maize plants, which is where the caterpillars mostly feed was explored. By treating maize with entomopathogenic nematode species, the number of surviving FAW larvae was significantly reduced. The most effective treatment was achieved using Steinernema carpocapsae (EGAZ10) (Weiser) (Rhabditida: Steinernematidae), which resulted in a decrease of FAW larvae by 80.3 ± 4.6% and 92.7 ± 2.2% in 2022 and 90.1 ± 2.9% and 93.3 ± 2.7% in 2023 after 5 and 10 days of treatment, respectively. Protecto 9.4% WP (Bacillus thuringiensis subsp. kurstaki) (Bulla et al.) (Bacillales: Bacillaceae) and Speedo 5.7% WG (Emamectin benzoate) also showed a high reduction of FAW, with a 76.9 ± 4.9% and 78.4 ± 5.1% reduction in 2022 and an increase to 84.5 ± 4% and 84.3 ± 3.8% reduction in 2023, respectively. Biossiana 2.5% WP (Beauveria bassiana) (Crivelli & Vuillemin) (Bacillales: Bacillaceae) resulted in a reduction of 70.9 ± 6.9% and 73.8 ± 6.4% in 2021 and 2022, respectively. Entomopathogenic agents such as entomopathogenic nematodes (EPNs), Protecto, Speedo, and Biossaina can be applied directly to a whorl plant to manage fall armyworm in an eco-friendly way. These results proved that entomopathogenic agents are good candidates for the biological control of FAW and can be a sustainable and safe alternative to synthetic insecticides. Conclusions Among the different entomopathogenic agents evaluated, S. carpocapsae (EGAZ10) and Heterorhabditis indica (EGAZ5) (Poinar, Karunakar & David) (Rhabditida: Heterorhabditidae) showed the highest FAW larval mortality at 2000 or 3000 IJs/ml. In the case of entomopathogenic bacteria (Protecto) and entomopathogenic fungus (Biossiana), significant larval mortality against S. frugiperda (FAW) was shown. Our research demonstrated that the use of entomopathogenic agents effectively reduced fall armyworm (FAW) populations in field conditions.